2023
DOI: 10.1155/2023/6868417
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiome Does Not Represent Whole Gut Microbiome

Abstract: The current gut microbiome research relies on the fecal microbiome under the assumption that the fecal microbiome represents the microbiome of the entire gastrointestinal (GI) tract. However, there have been growing concerns about using feces as a proxy to study the gut microbiome. Here, we comprehensively analyzed the composition of microbiome and metabolites in the feces and at 14 different locations of GI tracts of genetically homogenous sibling pigs to evaluate the validity of using feces as a proxy to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Total bacterial genomic DNA from each sample was extracted using the phenol-chloroform isoamyl alcohol extraction method as described previously [53,54]. Brie y, samples suspended in lysis buffer (200 mM NaCl, 200 mM Tris-HCl (pH 8.0), 20 mM EDTA) were processed by bead-beating.…”
Section: Dna Extraction and 16s Rrna Gene Sequencingmentioning
confidence: 99%
See 3 more Smart Citations
“…Total bacterial genomic DNA from each sample was extracted using the phenol-chloroform isoamyl alcohol extraction method as described previously [53,54]. Brie y, samples suspended in lysis buffer (200 mM NaCl, 200 mM Tris-HCl (pH 8.0), 20 mM EDTA) were processed by bead-beating.…”
Section: Dna Extraction and 16s Rrna Gene Sequencingmentioning
confidence: 99%
“…All Data and statistical analyses were determined as described previously [53,54]. In brief, the Q2-Feature classi er is a Naive Bayes classi er trained based on the SILVA reference (region V3-V4) database (https://www.arb-silva.de/) to classify bacterial species.…”
Section: Data and Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…The family of Lactobacillaceae and Enterobacteriaceae are dominant bacteria in the stomach and small intestine (i.e., duodenum, jejunum, and ileum), while Bacteroidaceae, Prevotellaceae, Rikenellacea, Lachnospiraceae, and Ruminococcaceae are major dominant families of bacteria in the large intestine [179]. In microbiome studies, it is important to note that a new experimental comparative study by Ji-Seon Ahn et al revealed that the fecal microbiome contents are not acceptable to be generalized to the entire gut microbiome [181].…”
Section: Box 2 Small Intestine Versus Large Intestine Microbiome Comp...mentioning
confidence: 99%